Psychosocial risk at work and mental illness in hospital workers - Elisa Ansoleaga M; Alvaro Castillo-Carniglia (Universidad de Antioquia, 2011)
There is growing evidence on the association between exposure to psychosocial risk at work and adverse health outcomes. Objective: to describe and analyze the presence of psychosocial risks at work and mental health symptoms in non-clinical workers from a public hospital. Methods: a crosssectional study was conducted at a public hospital in Santiago (Chile). A self-administered questionnaire was applied to assess exposure to psychosocial risks (demand-control and effort-reward imbalance models). The outcome variables were depression symptoms, anxiety symptoms, and psychotropic drug consumption. The analysis was descriptive and associative (Fisher's exact test) Results: 47% of the workers showed high psychological demands, 46% low autonomy, 61% low social support and 75% imbalance between effort expended and rewards received. The prevalence of depressive and anxious symptoms in the total sample was 10% and 30% respectively, while 25% reported having used psychotropic drugs. The consumption of psychotropic drugs was significantly higher (p < 0.05) among those with low social support and effort-reward imbalance. Discussion: the consumption of psychotropic drugs was associated with low social support and imbalance between efforts expended and rewards received. This might have implications in the workers' health and performance; therefore, further research is required, particularly on this kind of population, to understand this relationship and thus develop prevention programs in this regard.